Time-related morphometric studies on CD34 protein expression in the cerebral blood vessels after fatal brain contusions - Mariusz Kobek; Zbigniew Jankowski; Janusz Szala; Zbigniew Gąszczyk-Ożarowski; Artur Pałasz; Rafał Skowronek (Folia Neuropathologica, 2018)
In our previous work, we have discussed the importance of neurofilaments in determination of the age of brain contusions. The purpose of this paper is to examine a possibility of angiogenesis-related assessment of the age of brain contusions by means of morphometric analysis of the CD34 expression in the contused sites. The researched material comprised 90 cases divided into nine groups according to the time of death: immediately on the spot, 12 hours, 24 hours, 2 days, 3 days, 4 days, 5 days, 6 days, and 7 days after the head trauma. Immunohistochemically stained CD34 antigen was evaluated quantitatively with the Met-Ilo application. The results were then tested statistically for any regularities. Generally, there was a tendency to increase both the number of blood vessels and blood vessels area fraction in time. The results of Kruskal-Wallis analysis showed that numbers of blood vessels were significantly different in the first seven days after the head trauma, but significance levels of specific sample pairs, as calculated by Dunn’s test, were not statistically significant. Thus, the conclusion is that the proposed method is of no considerable value in determination of the age of brain contusions.